2006
DOI: 10.1038/sj.sc.3101898
|View full text |Cite
|
Sign up to set email alerts
|

Does repeated electro-ejaculation improve sperm quality in spinal cord injured men?

Abstract: Study design: Retrospective analysis. Objectives: To assess the effect of repeated electro-ejaculation on the sperm quality in spinal cord injured men. Setting: Regional Spinal Injuries Unit, Southport, UK and Hewitt Center for Reproductive Medicine, Liverpool, UK. Method: Retrospective, observational study of men with spinal cord injuries undergoing repeated electro-ejaculation as a part of fertility treatment. Result: There was no improvement in the volume, sperm concentration, motility or the total motile c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Prolonged anejaculation may induce the development of anti-sperm antibodies but the available evidence regarding their role in the development of male infertility after SCI is conflicting. On the other hand, repeated ejaculations do not change the spermatozoal quality of SCI men (Sonksen et al, 1999;Das et al, 2006). This fact may suggest that stagnation in the seminal ducts due to infrequent ejaculations is not the cause of the poor spermatozoal parameters in SCI men (Sonksen et al, 1999).…”
Section: Seminal Plasma Biochemistry and Scimentioning
confidence: 82%
“…Prolonged anejaculation may induce the development of anti-sperm antibodies but the available evidence regarding their role in the development of male infertility after SCI is conflicting. On the other hand, repeated ejaculations do not change the spermatozoal quality of SCI men (Sonksen et al, 1999;Das et al, 2006). This fact may suggest that stagnation in the seminal ducts due to infrequent ejaculations is not the cause of the poor spermatozoal parameters in SCI men (Sonksen et al, 1999).…”
Section: Seminal Plasma Biochemistry and Scimentioning
confidence: 82%
“…14 Beretta et al also observed improvement of sperm motility, after 3 months of weekly PVS. 22 Four other groups reported no significant improvement of semen parameters after repeated (electro)ejaculation; that is, Heruti et al, 4 Das et al, 11 Sonksen et al 17 and Siosteen et al 16 However, it remains debatable whether carrying out a second EEJ in men whose first ejaculates contain progressively motile spermatozoa is necessary at all. Since the introduction of ICSI, patients with severe oligoasthenospermia now have a realistic chance of conceiving.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not repeated (electro)ejaculation has a positive effect on semen quality remains debatable, as studies on this issue show contradictory results. 4,[11][12][13][14][15][16][17] Therefore, deciding on how many attempts of EEJ should be carried out before proceeding to surgical sperm retrieval remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…One study found improved sperm motility after 3 months of weekly PVS performed by patients at home (Beretta et al ., ). The majority of studies, however, found no statistically significant improvement in sperm motility after regular ejaculation by PVS or EEJ (Siosteen et al ., ; Sonksen et al ., ; Das et al ., ; Hamid et al ., ). Further, no study has found normalization of sperm motility in men with SCI by increasing the frequency of ejaculation.…”
Section: Semen Quality In Men With Scimentioning
confidence: 98%